Effectiveness of Combo Acupressure Points During the Menstrual Phase Against Dysmenorrhea in Adolescents: EFEKTIFITAS COMBO ACCUPRESSURE POINT PADA FASE MENSTRUASI TERHADAP DISMINORE PADA REMAJA - Hasanah, Oswati; Lestari, Widia; Novayelinda, Riri; Deli, Hellena (Program Studi Keperawatan Fakultas Kedokteran dan Ilmu Kesehatan Universitas Jambi, 2020)
Dysmenorrhea is a problem that is often occur among adolescent girls during menstruation. Dysmenorrhea in adolescents can cause impact to academic and daily activities, which in turn may have an impact on adolescent quality of life in the future. The purpose of this study was to determine the effectiveness of acupressure therapy at 3 points on the intensity of dysmenorrhea in adolescents. This research is a quantitative research, using a randomized clinical trial design. The study was conducted in Pekanbaru with the population were all female students of the Faculty of Nursing, at Riau University. A sample of 30 respondents divided into experimental group and the control group were selected based on inclusion and exclusion criteria. The measuring instrument used in this study consists of 2 parts. The first part is a structured questionnaire and the second part is the Visual Analogue Scale (VAS). The result shows, based on the age of most respondents were aged 18-19 years (53%). Based on ethnicity, most respondents have Malay ethnicity (43, 3%). Based on the results of the bivariate test analysis in both groups, combination acupressure at LR3, LI4 and Yintang points did not affect the decrease in pain intensity of dysmenorrhea if it was done in the menstrual phase (p-value> Î±), but there were significant differences in pain intensity before and after the intervention in the experimental and control group (p-value> Î±), which is 3.13 points in the experimental group when compared to the control group which is 2.53 points. The results of this study can recommend the use of acupressure as a nursing intervention or as an independent intervention for adolescents to overcome dysmenorrhea.